Model Pengembangan Digital Citizenshiip Pada Pembelajaran PKn - Rumiati, Sri; Pudjiastuti, Sri Rahayu; Karim, Aim Abdul; Darmawan, Cecep; Fitriasari, Susan (Universitas Negeri Malang, 2023)
This study aims to describe the role of civics learning based on digital citizenship development and the integration of digital citizenship models through civics learning. This study uses a qualitative approach with descriptive research type. The data collection technique uses the literature study method by reviewing various literature. The results of the study show that the role of civics learning based on digital citizenship development is as a strategy so that students have the qualities to be able to face the challenges of the times. The integration of the digital citizenship development model through civics learning is based on the behaviorist theory of operant conditioning, namely changes in student behavior caused by positive responses. The new concept of digital citizenship through civics learning must be implemented in the digital era so that teachers and students can use technology wisely and judiciously.